Self-Monitoring of Prothrombin Time Using a Portable Coagulation Monitor - Harenberg, J.; Kulinna, W.; Heene, D. L. (Hämostaseologie, 1997)
The CoaguChek® is a portable coagulation monitor, which uses disposable cartridges containing a lyophilized rabbit brain thromboplastin to measure the prothrombin time (PT) from capillary whole blood. Own studies in patients have demonstrated an improved quality of life after an 6 months experience with self-determination as well as an increase of the within-therapeutic range of measured INR values. The use of a portable monitor as the primary method for measuring the INR can be recommended in selected patients receiving long-term anticoagulant treatment.
Keywords: Oral anticoagulation; prothrombin time; self monitoring; coagulation monitor